2013
DOI: 10.1371/journal.pone.0052242
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Study Homogeneity of Psoriasis Gene Expression in Skin across a Large Expression Range

Abstract: BackgroundIn psoriasis, only limited overlap between sets of genes identified as differentially expressed (psoriatic lesional vs. psoriatic non-lesional) was found using statistical and fold-change cut-offs. To provide a framework for utilizing prior psoriasis data sets we sought to understand the consistency of those sets.Methodology/Principal FindingsMicroarray expression profiling and qRT-PCR were used to characterize gene expression in PP and PN skin from psoriasis patients. cDNA (three new data sets) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 25 publications
(64 reference statements)
5
63
0
1
Order By: Relevance
“…One portion of each biopsy was flash frozen in liquid nitrogen for RNA isolation as described previously (18). Briefly, while still frozen, biopsies were homogenized in lysis buffer with or without manual disruption and RNA was prepared using the mirVana miRNA Isolation kit (Applied Biosystems, Carlsbad, CA) with on-column DNase treatment (Qiagen, Valencia, CA).…”
Section: Biopsy Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…One portion of each biopsy was flash frozen in liquid nitrogen for RNA isolation as described previously (18). Briefly, while still frozen, biopsies were homogenized in lysis buffer with or without manual disruption and RNA was prepared using the mirVana miRNA Isolation kit (Applied Biosystems, Carlsbad, CA) with on-column DNase treatment (Qiagen, Valencia, CA).…”
Section: Biopsy Processingmentioning
confidence: 99%
“…A core set of genes differentially expressed between independently procured nonlesional and lesional skin was identified ("Core PsO") using 14 paired samples from the Asterand subset and 15 paired samples from the ZabaAmgen subset of the publically available microarray data set of paired lesional and nonlesional psoriasis samples (GSE41664) (18). A table of probe sets, log ratios, and p values was created from estimated between group differences in probe-set intensities provided by the AffyPLM:: threestep function using R version 2.15.2 (20,21).…”
Section: Microarray Data Analysismentioning
confidence: 99%
“…We identified 4 independent gene expression datasets from clinical trials in psoriasis using anti-TNF (etanercept; 2 independent datasets), anti-IL-23 (guselkumab), or anti-IL-17R (brodalumab) (48)(49)(50)(51). Consistent with the gene expression results in Figure 3, in these clinical trials, GRHL3 was significantly upregulated in lesional versus nonlesional skin, and after treatment, this high level was significantly reduced to levels similar to the nonlesional controls in all but 1 etanercept trial, which still showed the correct trend (Supplemental Figure 6, A-D).…”
Section: Grhl3 Is Dispensable For Homeostatic Adult Epidermal Barriermentioning
confidence: 99%
“…Several studies have examined the psoriasis-related transcriptome by comparing lists of differentially expressed genes with inconsistent results (Bigler et al, 2013;Gudjonsson et al, 2010;Suarez-Farinas et al, 2010). The absence of agreement between these studies might be due to threshold affects (e.g., p-value, fold change, false discovery rate) on selection of over-and underexpressed genes and also parameter differences in analyzing microarrays (Pan et al, 2005).…”
Section: Discussionmentioning
confidence: 99%